Income-augmenting interventions and food self-sufficiency for enhancing food consumption among the poor - Reutlinger, Shlomo (International Food Policy Research Institute, 1988)
Most governments implement policies or programs, such as food subsidies, to augment the incomes of disadvantaged groups in the population. Some interventions, such as unemployment insurance and public works programs, are clearly targeted to benefit specific disadvantaged groups. Other interventions, such as regional development schemes or the distribution of subsidized inputs, are less well targeted in the sense that a share (sometimes a large share) of the benefits are conveyed to persons whose incomes are well above the poverty threshold. Finally, there are the general trade intervention policies designed to raise the incomes of all the producers of certain commodities (or holders of assets used in the production of the commodities).